Pengaruh Pemberian Air Rebusan Pepaya Muda terhadap Peningkatan Produksi Air Susu Ibu Menyusui - Yussie Ater Merry; Elda Yusefni (CV. CENDIKIA JENIUS INDONESIA, 2024)
Breast milk (ASI) is a fluid secreted by the mother's breast glands, which is the first, main and best food for babies. The aim of this community service activity is to determine the effect of giving young papaya boiled water on increasing baby weight in breastfeeding mothers. The location of the activity is in Kurao Pagang Village, Nanggalo Health Center Working Area, Padang City. This activity was carried out on 23 September – 08 November 2019 with a target number of breastfeeding mothers of 33 people. The method for this activity is to provide counseling, discussions and demonstrations about problems surrounding breast milk production and how to boil young papaya fruit. Evaluation was carried out using pretest and posttest questionnaires and it was found that respondents' knowledge about issues surrounding breast milk was 100% and how to boil papaya to increase baby weight in breastfeeding mothers by 98%. Conclusion: There has been an increase in knowledge of breastfeeding mothers regarding issues surrounding 100% breast milk and how to boil papaya to increase baby weight in breastfeeding mothers. It is recommended that breastfeeding mothers practice the knowledge that has been given to increase breast milk production for breastfeeding mothers.